A Bibliometric Analysis of Indian Research on Quality Education (2005- 2024): Trends, Impact, and Future Directions (LIS TODAY, 2025)
This study examines research trends on quality education in India from 2005 to 2024  through bibliometric analysis, addressing the lack of a comprehensive understanding  of Indian research output in this critical area. Key aspects analyzed include publication  trends, leading authors, thematic areas, influential institutions, and prominent sources.  Data extracted from the Scopus database on November 22, 2024, yielded 654 publications,  analyzed using MS Excel and Bibliometrix R software. Findings reveal a notable rise in  publications, especially post-2020, with peaks in 2023 and 2024. Authors like Raghu  Raman and Priyadarshini Dey, along with institutions such as the University of Delhi  and Christ University, emerged as significant contributors. Dominant themes include  social sciences, computer science, and engineering, while popular keywords such as  “quality education” and “e-learning” reflect emerging trends. The study offers actionable  insights for policymakers, educators, and researchers to enhance collaborations, address  research gaps, and support sustainable educational development.
Keywords: Quality Education; Bibliometric Analysis; Indian Research; Research Trends; Higher Education